The human homolog of Escherichia coli endonuclease V is a nucleolar protein with affinity for branched DNA structures. - Cathrine Fladeby (Public Library of Science (PLoS), 2012)
Loss of amino groups from adenines in DNA results in the formation of hypoxanthine (Hx) bases with miscoding properties. The primary enzyme in Escherichia coli for DNA repair initiation at deaminated adenine is endonuclease V (endoV), encoded by the nfi gene, which cleaves the second phosphodiester bond 3' of an Hx lesion. Endonuclease V orthologs are widespread in nature and belong to a family of highly conserved proteins. Whereas prokaryotic endoV enzymes are well characterized, the function of the eukaryotic homologs remains obscure. Here we describe the human endoV ortholog and show with bioinformatics and experimental analysis that a large number of transcript variants exist for the human endonuclease V gene (ENDOV), many of which are unlikely to be translated into functional protein. Full-length ENDOV is encoded by 8 evolutionary conserved exons covering the core region of the enzyme, in addition to one or more 3'-exons encoding an unstructured and poorly conserved C-terminus. In contrast to the E. coli enzyme, we find recombinant ENDOV neither to incise nor bind Hx-containing DNA. While both enzymes have strong affinity for several branched DNA substrates, cleavage is observed only with E. coli endoV. We find that ENDOV is localized in the cytoplasm and nucleoli of human cells. As nucleoli harbor the rRNA genes, this may suggest a role for the protein in rRNA gene transactions such as DNA replication or RNA transcription.